Study on the Traffic Air Pollution inside and outside a Road Tunnel in Shanghai, China - Zhou, Rui (PLoS One, 2014)
To investigate the vehicle induced air pollution situations both inside and outside the tunnel, the field measurement of the pollutants concentrations and its diurnal variations was performed inside and outside the Xiangyin tunnel in Shanghai from 13:00 on April 24th to 13:00 on April 25th, 2013. The highest hourly average concentrations of pollutants were quantified that CO, NO, NO(2) and NO(X) inside the tunnel were 13.223 mg/m(3), 1.829 mg/m(3), 0.291 mg/m(3) and 3.029 mg/m(3), respectively, while the lowest ones were 3.086 mg/m(3), 0.344 mg/m(3), 0.080 mg/m(3) and 0.619 mg/m(3). Moreover, the concentrations of pollutants were higher during the daytime, and lower at night, which is relevant to the traffic conditions inside the tunnel. Pollutants concentrations inside the tunnel were much higher than those outside the tunnel. Then in a case of slow wind, the effect of wind is much smaller than the impact of pollution sources. Additionally, the PM(2.5) concentrations climbed to the peak sharply (468.45 µg/m(3)) during the morning rush hours. The concentrations of organic carbon (OC) and elemental carbon (EC) in PM(2.5) inside the tunnel were 37.09–99.06 µg/m(3) and 22.69–137.99 µg/m(3), respectively. Besides, the OC/EC ratio ranged from 0.72 to 2.19 with an average value of 1.34. Compared with the results of other tunnel experiments in Guangzhou and Shenzhen, China, it could be inferred that the proportion of HDVs through the Xiangyin tunnel is relatively lower.